(untitled) (Research, Society and Development, 2023)
The time spent with screens has increased over the years, mainly as a way to entertain children and adolescents, replacing social interactions and moments of conviviality that are important for development with the virtual world. Thus, notes continue to be taken about the possible consequences of this virtual interaction when it exceeds the maximum of two hours a day recommended by the Brazilian Society of Pediatrics. Based on this explanation, the objective of this work is a bibliographical review related to the physical and mental effects in young people with exacerbated screen time. The literature used as a source was found on Google Scholar, SCIELO, MEDLINE, EbscoHost platforms, with articles between 2016 and 2022 being chosen. It was possible to conclude that there is no compliance with the recommended screen time for certain age groups, and that this causes a lot of time inactive, associated with increased overweight, poor sleep quality, depression and anxiety, which suggests the need for intervention by those responsible for establishing a healthier routine together.